Analysis of Umrah Pilgrimage Service Strategies in Building a Positive Image at PT. Asyesa Hasanah Tour & Travel West Sumatra - Hasibuan, Nurkholijah; Rahmi, Rahmi (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2023)
The background of this research is the large number of hajj and umrah travel agencies that have been established in West Sumatra which has led to a high level of competition. Besides, there has been a decrease in the number of pilgrims due to Covid-19 and a lack of human resources (HR) at PT. Asyesa Hasanah Tour & Travel West Sumatra, causing a lack of effectiveness in providing services to pilgrims. The purpose of this study is to determine the umrah pilgrims' service strategy in building a positive image at PT. Asyesa Hasanah Tour& Travel West Sumatra. This study used a qualitative descriptive research method by collecting data using observation, interviews, and documentation. The results of this study indicate that the service strategy carried out by PT. Asyesa Hasanah Tour & Travel West Sumatra for Umrah pilgrims is to provide the best possible service starting from their homeland, Saudi Arabia to returning to their homeland, establish cooperation with other companies, establish a relationship with pilgrims, and provide guaranteed accommodation, transportation and the best prices. Meanwhile, the efforts made by PT. Asyesa Hasanah Tour & Travel West Sumatra to build a positive image are by forming a pilgrim alumni association, branding personnel within the company, and making promotions honestly.